Windrow composting of paddy straw - Elias, Azhani; Che Man, Hasfalina; Samsu Baharuddin, Azhari; Othman, Jamarei; Abdullah, Nurlidah (2012)
In this work, the profile windrow composting of paddy straw were investigated. The composting process was completed within 40 days and the final C/N ratio achieved was 11.7. The most gradually C/N ratio was observed during the thermophilic temperature range. The highest thermophilic temperature achieved was 73.4°C and the final nutrient content in terms of N, P and K were 2.8%, 0.4 % and 2.8% respectively. In conclusion, windrow composting was able to enhance the degradation process of paddy straw.